The relevance of implementing the employee digital profile as an element of the employer’s HR policy - O. V. Shcherbakova (Правоприменение, 2025)
The subject. Economic, technological and geopolitical changes are leading to the digitalization of virtually all structures of the labor market: from the process of production and human resources management to the organization of the workplace. The use of new digital technologies makes it possible to give up routine human labor, contribute to improving the quality of working life of employees and employers, and increase industrial production, which means economic growth of the state. Thus, in accordance with the National Security Strategy, approved by the Decree of the President of the Russian Federation dated July 2, 2021 No. 400, the situation in the production industry is one of the key criteria of Russia's competitiveness and contributes to the strengthening of the state's defense capability. Ensuring Russia's independence  and competitiveness was also announced to be the main goal of the Strategy for Scientific and Technological Development of the Russian Federation, approved by Presidential Decree No. 642 dated December 1, 2016. On the other hand, the use of new technologies may have time-delayed risks. The most important risk today is the increasing release of labor force and mass cuts of jobs requiring average qualifications, as well as dismissal of employees due to failure to pass tests because of the lack of skills in digital tools.The purpose of the study was to substantiate the urgent character of the implementation of digital profile programs as a part of the employer's personnel policy to achieve the objectives set in the National Security Strategy of the Russian Federation dated 2021.The methodology of comprehensive research, including methods of document analysis, comparative analysis, secondary use of sociological and economic data were used.Main results. The study shows that the use of the employee digital profile programs will allow the employer to identify weaknesses in any of the employee’s skills well in advance, and to pave individual learning pathway, based on his/her preferences, hobbies  and intentions, in order to upgrade the skills. It is deemed that the competence of employees is a factor for transfer of any business to digitalization. This policy of the employer will allow to cover for low-quality job cut and give personnel the minimum knowledge that makes it possible to acquire information on modern information technologies, be able to use it to solve the set problems and have necessary skills and technology, which will facilitate solution of the problems. Ultimately, these are tools to achieve the tasks set by the state in the framework of the state's defensive capability and competitiveness. At the same time, the lack of normative methodologies for the creation and operation of employee digital profiles and comprehensive scientific research predetermine increasing risks of violation of personal data of employees, privacy of employees, as well as discrimination in making legally significant decisions. Today there are no normative standards of data processing and system interaction, which leads to the diminution of guarantees of employees' rights in terms of respect for personal data and other data in terms of classified information.